Enhancing the Effectiveness of Midwifery Services Through UI/UX Design of an Electronic Medical Record System in Independent Midwife Practices - Desi Syahbaniar; Carolina Gloria Oru Ndaya; Eny Yuniyati (Nusantara Sehat: Jurnal Kesehatan Indonesia, 2026)
ABSTRACT The implementation of medical records at the Qopitinia Independent Midwife Practice is still carried out manually, making the service process and patient data management inefficient. This study aims to design a User Interface (UI) and User Experience (UX) for a web-based electronic medical record system specifically for independent midwife practices. The research method used is Research and Development (R&D) with the Activity-Centered Design (ACD) approach, which focuses on user activities, and includes a design evaluation using the User Experience Questionnaire (UEQ). The results indicate that the designed web-based electronic medical record application can assist midwife practices in managing registration, examination, and reporting data digitally and in an integrated manner. The UEQ evaluation showed good to excellent scores, with Perspicuity obtaining the highest rating. In conclusion, the application designed using the UI/UX approach and user-activity focus demonstrated a very good user experience, particularly in the Perspicuity dimension, which received the highest score in the Excellent category. It is recommended that the Qopitinia Independent Midwife Practice implement the electronic medical record system to improve data recording and reporting. KEYWORDS: Electronic Medical Records (EMR); UI/UX, Independent Midwife Practice (IMD); Activity Centered Design (ACD); User Experience Questionnaire (UEQ)